(untitled) (Majalah Kedokteran Bandung, 2019)
Polycystic ovary syndrome (PCOS) is the most common endocrine abnormality in reproductive-age women, which is characterized by hyperandrogenism, anovulation, and polycystic ovaries. Some evidence suggested that leptin also causes PCOS due to its role in female reproductive system. The physiological function of leptin controls the balance of energy and suppresses the center of appetite. Patients with PCOS maybe underweight, normoweight, overweight, and obese, based on their body mass index (BMI), but obesity is a common clinical situation in PCOS. Obesity occurs when the level of leptin increases but cannot decrease appetite, resulting in leptin resistance. This study aimed to discover the connection between BMI and the level of leptin in patients with PCOS. This was a cross-sectional observational analytic performed in Dr. Hasan Sadikin General Hospital Bandung between April 25 and July 10, 2018. Subjects included 46 PCOS patients who were diagnosed based on Rotterdam criteria by gynecology obstetricians in the hospital. Enzyme-linked immunosorbent assay (ELISA) was used to examine the leptin serum levels. Leptin level increased 74%, mostly in obese patients that comprised 41% of these subjects. Normal leptin levels was seen in 26% of patients, none of them was obese. The Spearman Rank correlation test showed a significant positive correlation between BMI and leptin levels (r=0.644, p=0.000). Hence, a high body mass index in people with PCOS positively correlates with increased leptin level. Korelasi antara Indeks Massa Tubuh dan Kadar Leptin Serum pada Penderita Sindrom Ovarium Polikistik Sindrom Ovarium Polikistik (SOPK) merupakan kelainan endokrin pada wanita reproduktif yang ditandai oleh hiperandrogenisme, anovulasi, dan ovarium polikistik. Terdapat beberapa bukti bahwa leptin turut menyebabkan SOPK karena leptin berperan dalam sistem reproduksi wanita. Fungsi fisiologis leptin mengendalikan keseimbangan energi dan menekan pusat nafsu makan. Penderita SOPK dapat memiliki indeks massa tubuh (IMT) underweight, normoweight, overweight dan obese, namun obesitas merupakan gambaran klinis yang umum terjadi pada SOPK. Obesitas terjadi bila peningkatan kadar leptin, namun leptin tidak mampu bekerja menurunkan nafsu makan sehingga terjadi resistensi leptin. Penelitian ini bertujuan mengetahui hubungan IMT dengan kadar leptin pada penderita SOPK. Penelitian ini berbentuk analitik observasional dengan rancangan potong lintang dan dilakukan di Rumah Sakit Umum Pusat Dr. Hasan Sadikin (RSHS) Bandung pada tanggal 25 April–10 Juli 2018. Subjek penelitian sebanyak 46 penderita SOPK yang didiagnosis berdasar atas kriteria Rotterdam oleh klinisi obstetri ginekologi RSHS. Pemeriksaan kadar leptin serum mengunakan metode Enzyme-linked immunosorbent assay (ELISA). Kadar leptin yang meningkat 74% terbanyak pada IMT obese 41% subjek, dan kadar leptin normal 26% tidak ditemukan pada subjek yang IMT obese. Uji korelasi Rank Spearman menunjukkan korelasi positif kuat yang bermakna antara IMT dan kadar leptin (r=0,644; p=0,000). Indeks massa tubuh yang tinggi pada penderita SOPK berkorelasi positif dengan peningkatan kadar leptin.